2016
DOI: 10.1164/rccm.201509-1722pp
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibrinogen Qualification as a Drug Development Tool in Chronic Obstructive Pulmonary Disease. Perspective of the Chronic Obstructive Pulmonary Disease Biomarker Qualification Consortium

Abstract: The COPD Foundation Biomarker Qualification Consortium (CBQC) is a unique public-private partnership established in 2010 between the COPD Foundation, the pharmaceutical industry, and academic chronic obstructive pulmonary disease (COPD) experts with advisors from the U.S. NHLBI and the Food and Drug Administration (FDA). This was a direct response to the 2009 publication of a guidance on qualification of drug development tools by the FDA. Although data were believed to be available from publicly funded and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 32 publications
1
78
1
4
Order By: Relevance
“…Funding source: The study was funded by the CBQC using funds contributed by 4 Industry members (Astra Zeneca, Boehringher Ingleheim, GSK and Novartis) and managed by the nonprofit COPD Foundation (2). The role of the funding source was to provide the funds needed for the analysis and for the meetings needed to complete the project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Funding source: The study was funded by the CBQC using funds contributed by 4 Industry members (Astra Zeneca, Boehringher Ingleheim, GSK and Novartis) and managed by the nonprofit COPD Foundation (2). The role of the funding source was to provide the funds needed for the analysis and for the meetings needed to complete the project.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of biomarkers and clinical measures that can determine the degree of overall impairment, help prognosticate outcome and reflect disease progression or regression in COPD is highly desirable. The regulatory qualification of drug development tools to help in the stratification of patients for potential inclusion in clinical trials is a major goal of the COPD biomarker qualification consortium (CBQC) which achieved its first successful qualification of plasma fibrinogen in 2015 (2).…”
Section: Introductionmentioning
confidence: 99%
“…The COPD Foundation Biomarker Qualification Consortium showed that patients with elevated levels of fibrinogen had a nearly two-fold increased risk of death from any cause over 3 years [21]. This led to the United States Food and Drug Administration qualification of plasma fibrinogen as a prognostic biomarker for all-cause mortality and COPD exacerbations.…”
Section: Biomarkersmentioning
confidence: 99%
“…Although our analysis does not allow us to have insight into the mechanisms linking low muscle mass and all-cause mortality, prior data in patients with COPD suggested that one of potential mechanisms is systemic inflammation. COPD subjects with elevated levels of plasma fibrinogen -a blood biomarker for systemic inflammation- had low FFM[2], and higher risk of death compared to those with low fibrinogen levels[35]. Another possibility is that low muscle mass might reflect decreased physical activity, which in turn is associated with increased all-cause mortality[36].…”
Section: Discussionmentioning
confidence: 99%